2016
DOI: 10.1088/0031-9155/61/11/4316
|View full text |Cite
|
Sign up to set email alerts
|

Red marrow and blood dosimetry in131I treatment of metastatic thyroid carcinoma: pre-treatment versus in-therapy results

Abstract: Treatment with radioiodine is a standard procedure for patients with well-differentiated thyroid cancer, but the main approach to the therapy is still empiric, consisting of the administration of fixed activities. A predictive individualized dosimetric study may represent an important tool for physicians to determine the best activity to prescribe. The aim of this work is to compare red marrow and blood absorbed dose values obtained in the pre-treatment (PT) dosimetry phase with those obtained in the in-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
2
5
0
1
Order By: Relevance
“…Even if clinical data have not yet demonstrated the therapeutic effectiveness of higher activities, some authors have suggested that high-activity single therapy may result in a higher efficacy than multiple low-activity treatments, because of the potential for smaller fractionated doses to increase the radio-resistance of metastatic tumors [2]. Moreover, Giostra et al [21] found that the administered therapeutic activity could be safely increased compared to the current prescribed activities (from 7.4 GBq to 11.1 GBq). Dorn et al [22] combined red marrow and lesion dosimetry showing that high-activity administrations with less than 3 Gy to the red marrow are a safe and more effective method with respect to fixed activity administrations.…”
Section: Discussionmentioning
confidence: 99%
“…Even if clinical data have not yet demonstrated the therapeutic effectiveness of higher activities, some authors have suggested that high-activity single therapy may result in a higher efficacy than multiple low-activity treatments, because of the potential for smaller fractionated doses to increase the radio-resistance of metastatic tumors [2]. Moreover, Giostra et al [21] found that the administered therapeutic activity could be safely increased compared to the current prescribed activities (from 7.4 GBq to 11.1 GBq). Dorn et al [22] combined red marrow and lesion dosimetry showing that high-activity administrations with less than 3 Gy to the red marrow are a safe and more effective method with respect to fixed activity administrations.…”
Section: Discussionmentioning
confidence: 99%
“…Implicit in all such approaches is the biokinetics assessed pre-treatment with a tracer activity and that of the in-treatment therapeutic administration are the same. To verify this assumption, a recent study [ 151 ] compared red marrow and blood absorbed dose values obtained pre-treatment with that obtained in-treatment for a group of 50 patients treated for metastatic thyroid cancer, using different dosimetric approaches: pre-treatment and in-treatment absorbed dose values to blood and red marrow appeared to be well correlated irrespective of the dosimetric approach used. In a retrospective analysis of 124 metastatic DTC patients who underwent dosimetric evaluation over a period of 15 y, the MTA approach was adopted using a risk-adapted approach [ 122 ]: the maximum administered activity was limited with radiation doses of 3 Gy to the red marrow or 30 Gy to the lungs, both limiting values corresponding to the absorbed dose of the external radiation therapy which is associated with a 5% risk of severe damage within 5 y. Eighty-three patients received 104 treatments, of which 13 were given for postsurgical ablation of thyroid remnants, 41 were given with curative intent, and 50 were for palliation (for the others, treatment resulted not indicated).…”
Section: Personalized Dosimetry In Radioiodine Therapy For Differenti...mentioning
confidence: 99%
“…Whereas, the D RM is the sum of two contributions: (I) direct irradiation due to blood activity (self blood contribution) and (II) indirect irradiation due to rest of body activity. It has been calculated using the formula reported in (15,16):…”
Section: Wb/rm Dosimetrymentioning
confidence: 99%
“…where I Ant and I Post represent counts inside lesion's ROI in anterior and posterior views respectively, corrected for background; f j is the self attenuation correction; C and μ(I-131) are the sensitivity of the gamma camera and the attenuation coefficient for 131 I obtained using an abosolute quantification described in (15,21) and are equal to 12.83 cps/MBq and 0.106 cm −1 , respectively. Finally the absorbed dose to lesion (D Lesion ) was calculated using the formula:…”
Section: Lesion Dosimetrymentioning
confidence: 99%